KOPERASI MEMBANGUN KARAKTER BANGSA (Sebuah Kajian Filosofis) - Norbertus Jegalus (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2020)
Two political economy thoughts that dominated the 19th and 20th centuries are liberalism and socialism. These two great ideologies originate from a philosophy that emphasizes individuality (liberalism) and another philosophy that emphasizes collectivity (socialism). These two ideologies face each other and have produced a world socio-economic order for approximately two centuries, where the influence we still experience today in Indonesia and that is what appears in the constitution of the Republic of Indonesia. Starting from the socio-economic order stated in the constitution, in the following we can review three fundamental political characteristics of the nation, namely the ideology of the nation state, the Pancasila State, and the unitary state. The existence of these three political entities - if we really examine the constitutional normative message about the national economy and social welfare - can only be guaranteed by cooperatives. Cooperatives as the pillars of the national economy can shape and guarantee the three Indonesian political characteristics.